PENGEMBANGAN ALAT PERAGA SEDERHANA GERAK PARABOLA (ALGAPA) PADA SISWA KELAS X SMA - Shabrina, Elsa; Novianto, Bayu Abdillah; Lestari, Diah Ayu; Astuti, Irnin Agustina Dwi (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2024)
This study aims to develop a simple teaching aid for parabolic motion material (ALGAPA) in class X SMA. This research is an R and D research which refers to the opinion of Sugiyono. The data collection instrument used in the form of a questionnaire given to material experts and practitioners to test the feasibility of simple parabolic motion props. The type of data produced is qualitative data which is analyzed by using the criteria for the assessment category to determine product quality. The results of this study, namely that a simple parabolic motion material in class X SMA has been developed which is suitable to be used as a learning medium and a tool for simple practicum with the results of the validation of material experts of 92.63% and expert practitioners of 86.36%.Kata Kunci: Alat Peraga Fisika, Gerak Parabola, Penelitian RD, Media Pembelajaran